Longitudinal assessment of loss and gain of lung function in childhood asthma - Mahut, Bruno; Bokov, Plamen; Beydon, Nicole; Delclaux, Christophe (The Journal of asthma, 2023)
The Childhood Asthma Management Program revealed that 25.7% of children with mild to moderate asthma exhibit loss of lung function. The objective was to assess the trajectories of function by means of serial FEV 1 in asthmatic children participating in out-of-hospital follow-up. A total of 295 children (199 boys) who had undergone at least 10 spirometry tests from the age of 8 were selected from a single-center open cohort. The annualized rate of change (slope) for prebronchodilator FEV 1 (percent predicted) was estimated for each participant and three patterns were defined: significantly positive slope, significantly negative slope, and null slope (non-significant P-value; Pearson test). The standard deviation (SD) of each individual slope was recorded as a variability criterion of FEV 1 . The median (25 th ; 75 th percentile) age at inclusion and the last visit was 8.5 (8.2; 9.3) and 15.4 (14.8, 16.0) years, respectively. Tracking of function (null slope) was observed in 68.8% of the children, while 27.8% showed a loss of function or reduced growth (negative slope) and 3.4% showed a gain in function (positive slope). The children characterized by loss of function depicted a better initial function and a lower FEV 1 variability during their follow-up than children with tracking or gain of lung function. At the last visit, these children were characterized by a lower lung function than children with tracking or gain of lung function. Better initial FEV 1 value and less FEV 1 variability are associated with loss of lung function or reduced lung growth in asthmatic children.